PELATIHAN PENYUSUNAN LAPORAN KEUANGAN PADA UMKM KECAP DEWI-DEWI Di KELURAHAN DUKUH SUTOREJO - Diana, Laksmi; Aulia, Dinda; Monica Dewi, Akwila; Putri, Rentaulina (CV. Era Digital Nusantara, 2022)
Usaha Mikro, Kecil, dan Menengah (UMKM) are pillars that support the nation’s economic growth. The existence of UMKM in Indonesia has an important and strategic impact on the Indonesian economy. With the existence of dominant UMKM, UMKM need to improve their quality by recording their financial statements properly. However, in reality, many UMKM have not been able to present their financial reports properly. So that we do this service to create UMKM that can do simple bookkeeping for their businesses. In Dukuh Sutorejo Village, there are at least 10 UMKM and 1.000 UKM engaged in various business fields, such as food and beverages, services, handicrafts, grocery stores and so on. Simple financial bookkeeping is only done by recording the number of transactions without recording the posts according to the department. The bookkeeping training provided to UMKM Kecap Dewi-Dewi was divided into two events, namely manually and using a digital application in the form of a “Buku Kas”. So that with this training, it is hoped that UMKM will be able to produce good routine bookkeeping for their businesses.